COVID-19 vaccine acceptance and its socio-demographic and emotional determinants: A multi-country cross-sectional study. Issue 2 (9th January 2023) - de Figueiredo, A.; Simas, C.; Larson, H.J.
Abstract: Background: Multiple COVID-19 vaccines have now been licensed for human use, with other candidate vaccines in different stages of development. Effective and safe vaccines against COVID-19 have been essential in achieving global reductions in severe disease caused by severe acute respiratory coronavirus 2 (SARS-CoV-2), but multiple factors, including vaccine supply and vaccine confidence, continue to impact global uptake of COVID-19 vaccines. In this study, we explore determinants of COVID-19 vaccination intent across17 countries worldwide. Methods: In this large-scale multi-country study, we explored intent to accept a COVID-19 vaccine and the socio-demographic and emotional determinants of uptake for 17 countries and over 19, 000 individuals surveyed in June and July 2020 via nationally representative samples. We used Bayesian ordinal logistic regressions to probe the relationship between intent to accept a COVID-19 vaccine and individuals' socio-demographic status, their confidence in COVID-19 vaccines, and their recent emotional status. Gibbs sampling was used for Bayesian model inference, with 95% Bayesian highest posterior density intervals used to capture uncertainty. Findings: Intent to accept a COVID-19 vaccine was found to be highest in India, where 77⋅8% (95% HPD, 75⋅5 to 80⋅0%) of respondents strongly agreeing that they would take a new COVID-19 vaccine if it were available. The Democratic Republic of Congo (15⋅5%, 12⋅2 to 18⋅6%) and France (26⋅4%, 23⋅7 to 29⋅2%) had the lowest share of respondents who strongly agreed that they would accept a COVID-19. Confidence in the safety, importance, and effectiveness of COVID-19 vaccines are the most widely informative determinants of vaccination intent. Socio-demographic and emotional determinants played a lesser role, with being male and having higher education associated with increased uptake intent in five countries and being fearful of catching COVID-19 also a strong determinant of uptake intent. Interpretation: Barriers to COVID-19 vaccine acceptance are found to be country and context dependent. These findings highlight the importance of regular monitoring of COVID-19 vaccine confidence to identify groups less likely to vaccinate.